MSME Development in Medan Krio Village, Deli Serdang Regency - Rivanka, Weny; Nawawi, Zuhrinal M. (Universitas Ibn Khaldun, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a significant role in improving the Indonesian economy, contributing greatly to national economic growth. The government actively encourages the development of MSMEs to increase overall economic growth and optimize the potential of MSMEs, both at the national and village levels. Pekarungan Village, especially Medan Krio Village, has great potential in MSMEs with 246 business actors consisting of the culinary sector, product sales, and services. However, Medan Krio Village does not yet have a policy or program focused on developing MSMEs. In the development of MSMEs, cooperation between business actors (internal) and government (external) is considered important to optimize potential and improve the economy. This study used a descriptive qualitative approach with data collection techniques through observation and interviews. The focus of the research is to explore the development of MSMEs in Medan Krio Village and how cooperation between business actors and the government can increase the economic potential of the village.